2016
DOI: 10.1016/j.neurobiolaging.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between axonal damage and demyelination in healthy aging by combining diffusion-tensor imaging and diffusion-weighted spectroscopy in the human corpus callosum at 7 T

Abstract: Diffusion-tensor imaging and single voxel diffusion-weighted magnetic resonance spectroscopy were used at 7T to explore in vivo age-related microstructural changes in the corpus callosum. Sixteen healthy elderly (age range 60-71 years) and 13 healthy younger controls (age range 23-32 years) were included in the study. In healthy elderly, we found lower water fractional anisotropy and higher water mean diffusivity and radial diffusivity in the corpus callosum, indicating the onset of demyelination processes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
2
22
1
Order By: Relevance
“…Our findings are consistent with those reported by Hikishima et al using a marmoset model treated with MPTP [24]. The increased ADC value indicated a significant increase in the radial diffusivity of water molecules within the nigrostriatal fibres, suggesting that demyelination occurs [2528]. The LFB staining confirmed that demyelination occurred in the TaClo-treated group, but not in the control group consistent with the DTI results.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those reported by Hikishima et al using a marmoset model treated with MPTP [24]. The increased ADC value indicated a significant increase in the radial diffusivity of water molecules within the nigrostriatal fibres, suggesting that demyelination occurs [2528]. The LFB staining confirmed that demyelination occurred in the TaClo-treated group, but not in the control group consistent with the DTI results.…”
Section: Discussionsupporting
confidence: 92%
“…One of the major discoveries involving G93A-SOD1 mice is that ALS is not cell specific, which means that glial cells surrounding motor neurons are probably involved in the mechanisms leading to the selective death of motor neurons, 70 and specific differences have been described between axonal damage and reduction in myelin content using DTI. 41,71,72 In particular, our study aimed to unveil the role of RD and myelin degeneration in ALS at earlier stages of the disease. 70,73 Consistent with previous reports of oligodendrocyte impairments in ALS, 73,74 our investigations determined a presymptomatic increase in RD associated with an early reduction in MBP in YFP,G93A-SOD1 mice (Figure 4a, b).…”
Section: Discussionsupporting
confidence: 91%
“…One of the major discoveries involving G93A‐SOD1 mice is that ALS is not cell specific, which means that glial cells surrounding motor neurons are probably involved in the mechanisms leading to the selective death of motor neurons, and specific differences have been described between axonal damage and reduction in myelin content using DTI . In particular, our study aimed to unveil the role of RD and myelin degeneration in ALS at earlier stages of the disease .…”
Section: Discussionmentioning
confidence: 99%
“…Hampshire, Chamberlain, Monti, Duncan, and Owen () reported that the role of rIFG is primarily in the provision of attention to relevant cues, and is recruited to the same extent regardless of whether cue detection is followed by either successful or unsuccessful inhibition. Although our findings pertaining to age‐related compensation could be interpreted as reflecting normal age‐related changes in rIFG, it is unlikely to be the case given that demyelination does not occur until later in life, and thus would not yet have affected our sample (Branzoli et al., ; Peters, , ). This could provide an interesting line of investigation for future studies to consider whether rIFG delivers the same compensatory mechanism in proactive inhibition after normal dopamine loss in healthy ageing, thus contributing further evidence to the topography of the effect we have reported here.…”
Section: Discussionmentioning
confidence: 82%